Modeling Cyclosporine A Inhibition of the Distribution of a P-Glycoprotein PET Ligand, (11)C-Verapamil, into the Maternal Brain and Fetal Liver of the Pregnant Nonhuman Primate: Impact of Tissue Blood Flow and Site of Inhibition - Ke, Alice Ban (J Nucl Med, 2013)
Through PET imaging, our laboratory has studied the dynamic biodistribution of (11)C-verapamil, a P-gp substrate, in the non-human primate Macaca nemestrina. To gain detailed insight into the kinetics of verapamil transport across the blood–brain barrier (BBB) and the blood–placental barrier (BPB), we analyzed these dynamic biodistribution data by compartmental modeling. METHODS: Thirteen pregnant macaques (gestational age, 71–159 d; term, ~172 d) underwent PET imaging with (11)C-verapamil before and during infusion (6, 12, or 24 mg/kg/h) of cyclosporine A (CsA, a P-glycoprotein [P-gp] inhibitor). Dynamic (11)C-verapamil brain or fetal liver (reporter of placental P-gp function) activity was assessed by a 1- or 2-tissue-compartment model. RESULTS: The 1-tissue-compartment model best explained the observed brain and fetal liver distribution of (11)C-radioactivity. When P-gp was completely inhibited, the brain and fetal liver distribution clearance (K(1)) approximated tissue blood flow (Q); that is, extraction ratio (K(1)/Q) was approximately 1, indicating that in the absence of P-gp function, the distribution of (11)C-verapamil radioactivity into these compartments is limited by blood flow. The potency of CsA to inhibit P-gp was tissue-independent (maternal BBB half-maximal inhibitory concentration [IC(50)], 5.67 ± 1.07 μM, vs. BPB IC(50), 7.63 ± 3.16 μM). CONCLUSION: We propose that on deliberate or inadvertent P-gp inhibition, the upper boundary of increase in human brain (or fetal) distribution of lipophilic drugs such as verapamil will be limited by tissue blood flow. This finding provides a means to predict the magnitude of P-gp–based drug interactions at the BBB and BPB when only the baseline distribution of the drug (i.e., in the absence of P-gp inhibition) across these barriers is available through PET. Our data suggest that P-gp–based drug interactions at the human BBB and BPB can be clinically significant, particularly for those P-gp substrate drugs for which P-gp plays a significant role in excluding the drug from these privileged compartments.